2023
DOI: 10.3390/microorganisms11092239
|View full text |Cite
|
Sign up to set email alerts
|

Co-Circulation of SARS-CoV-2 and Other Respiratory Pathogens in Upper and Lower Respiratory Tracts during Influenza Season 2022–2023 in Lazio Region

Licia Bordi,
Antonella Vulcano,
Giuseppe Sberna
et al.

Abstract: Lower respiratory tract infections (LRTIs) occur when there is a lower airway tract infection. They are well-known for increasing the susceptibility of patients to bacterial/fungal co-infections and super-infections. In this study, we present the results of our investigation, which involved 381 consecutive patients admitted to our hospital during the Influenza season from October 2022 to April 2023. Among the 381 specimens, 75 were bronchoalveolar (BAL), and 306 were nasopharyngeal swabs (NPSs). Notably, 34.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many studies conducted during the COVID-19 pandemic reported possible coinfections of SARS-CoV-2 with other respiratory pathogens, including bacteria, fungi, and viruses [ 12 , 34 , 35 ]. In our three-year follow-up study, a rate of 7.2% of coinfections was detected, which is consistent with other reports [ 4 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies conducted during the COVID-19 pandemic reported possible coinfections of SARS-CoV-2 with other respiratory pathogens, including bacteria, fungi, and viruses [ 12 , 34 , 35 ]. In our three-year follow-up study, a rate of 7.2% of coinfections was detected, which is consistent with other reports [ 4 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was not until the later years of the pandemic that more aggregated data were published defining the role of such infections during the peaks and troughs in confirmed SARS-CoV-2 cases [ 10 , 11 ]. Globally, the incidence of such mixed infections between seasonal respiratory viruses and SARS-CoV-2 during the pandemic ranged from 3% to 8% [ 12 , 13 , 14 , 15 ]. However, data on the prevalence and role of coinfections between SARS-CoV-2 and other respiratory viruses are limited [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%